2019
DOI: 10.1002/cam4.2319
|View full text |Cite
|
Sign up to set email alerts
|

Intensity‐Modulated Proton and Carbon‐Ion Radiation Therapy in the Management of Head and Neck Sarcomas

Abstract: Purpose We report our experience of intensity‐modulated proton and carbon‐ion radiotherapy (IMPT/IMCT) for head and neck sarcomas (HNS). Methods and Materials An analysis of the ongoing prospective data registry from the Shanghai Proton and Heavy Ion Center (SPHIC) for patients with HNS was conducted. The 12‐ and 24‐month rates of local recurrence‐free, overall, distant metastasis‐free, progression‐free survival (LRFS, OS, DMFS, and PFS), and acute/late toxicities were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Ionization radiation beams of higher LET have been shown to induce more complex DNA damage, despite reportedly more effective in eradicating tumor cells under hypoxic environment, as compared to those with lower LET (23)(24)(25)(26)(27). Theoretically, the physical and biological advantages of carbon ion radiation therapy (CIRT) make it more appropriate in the management of bulky or radio-resistant tumors (28)(29)(30). Results of pre-clinical or retrospective studies have confirmed its advantages in tumor proliferation and metastasis over photon (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Ionization radiation beams of higher LET have been shown to induce more complex DNA damage, despite reportedly more effective in eradicating tumor cells under hypoxic environment, as compared to those with lower LET (23)(24)(25)(26)(27). Theoretically, the physical and biological advantages of carbon ion radiation therapy (CIRT) make it more appropriate in the management of bulky or radio-resistant tumors (28)(29)(30). Results of pre-clinical or retrospective studies have confirmed its advantages in tumor proliferation and metastasis over photon (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Also, particle beams with higher linear energy transfer (e.g., carbon ion) produces significantly higher biological effectiveness as compared with photon beams (23), a clear advantage for radioresistant histologies such as most subtypes of sarcomas. Clinical data from several retrospective studies showed that PBRT could achieve favorable disease control for head and neck sarcomas or base of skull tumors, including chordoma and chondrosarcoma, even in patients with unresected or recurrent diseases (24)(25)(26)(27)(28)(29). In our previous studies, PBRT for head and neck sarcomas, including those involving skull base, produced effective tumor controls, and overall survivals in both primary and recurrent patients; the 1/2-year OS and LRFS for the entire cohort were 92.9/90.0 and 88.4/78.9%, respectively (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data from several retrospective studies showed that PBRT could achieve favorable disease control for head and neck sarcomas or base of skull tumors, including chordoma and chondrosarcoma, even in patients with unresected or recurrent diseases ( 24 29 ). In our previous studies, PBRT for head and neck sarcomas, including those involving skull base, produced effective tumor controls, and overall survivals in both primary and recurrent patients; the 1/2-year OS and LRFS for the entire cohort were 92.9/90.0 and 88.4/78.9%, respectively ( 24 , 25 ). For chondrosarcoma of the skull base, PBRT attained more favorable outcomes; results from Heidelberg Ion Beam Therapy Center reported both the 5-year OS, and local controls were over 90% and over 85%, respectively ( 26 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CIRT has been used to treat several tumors of the head and neck area. It has not been employed for squamocellular carcinoma-the most common entity-but rather, for other, radioresistant histologies, such as salivary gland tumors [15][16][17][18][19][20][21][22], paranasal sinuses tumors (including sinonasal undifferentiated carcinoma, sinonasal adenocarcinoma, intestinal-type adenocarcinoma, and esthesioneuroblastoma, among others) [15,23], mucosal melanoma [24][25][26][27][28], lacrimal gland tumors [29][30][31], and bone and soft tissue sarcoma (including tumors of the skull base and cervical spine [32][33][34][35][36][37][38] At MedAustron, CIRT was begun in July 2019. Until September 2020, 91 patients have been treated and 42 of them had tumors in the head and neck.…”
Section: Cirt Protocols For Head and Neck In Medaustronmentioning
confidence: 99%